PYTHON TOOLS FOR DATA SCIENTISTS POCKET PRIMER - CAMPESATO, OSWALD (MERCURY LEARNING & INFORM, 2022)
"This book contains a fast-paced introduction to as much relevant information about Python tools for data scientists as possible that can be reasonably included in a book of this size. If you are a novice, this book will give you a starting point from which you can decide which Python technologies that you want to explore in greater detail. You will be exposed to features of Numpy and Pandas, how to write regular expressions, and how to perform data cleaning tasks. Some topics are presented in a cursory manner, which is for two main reasons. First, it's important that you be exposed to these concepts. In some cases you will find topics that might pique your interest, and hence motivate you to learn more about them through self-study; in other cases you will probably be satisfied with a brief introduction. In other words, you will decide whether or not to delve into more detail regarding each of the topics in this book"-- Provided by publisher.
Keywords: Computer programming.; Electronic data processing.; Python (Computer program language); elektronické knihy; electronic books